Finite Element Analysis of Arc Guide Rail Measurement Simulator - Yue Yinpeng; Ou Kailiang; Tian Ye; He Bin (Jixie chuandong)
A new arc guide rail measurement simulator is introduced,the finite element model of this simulator is established by using the software ANSYS Workbench. A bearing equivalent stiffness treatment method adjusted to finite element program is introduced. The maximum stress and deformation are obtained by statics analysis,and the results could provide data support for structure improvement and weight reduction. The natural frequency and vibration type of measurement simulator in different condition are obtained by modal analysis,and the working reliability of it is proved.